Exploring Conjectural Perspectives of Evaluation as an Integral Part of the Project Management Cycle - Sandhu, Kiran; Ariyawansa, R. G. (Prabandhan: Indian Journal of Management, 2010)
Projects and programmes have since long been recognized as the most practical methodologies of achieving specific goals and objectives that may lead to progress and development (Cusworth and Franks,1993) and within the sphere of project management, the project cycle is recognized as an indispensable tool that guides the project systematically from its conception to the finish stage. In the sphere of project management, the word 'success' is used in the context of achieving something desirable i.e., the delivery of the project results on time, within budget and having an 'operational fit' with the organization's goals (Cleland and Ireland,2000). As such a stage of the project cycle -that can help arriving at judgments on a project's fate, its success or failures, merits or weaknesses, is the stage of evaluation.